Review of Islamic Criminal Law and Positive Regarding Combined Criminal Acts (Case Analysis Study of TNI AL Bintara Candidates in Padang) - Ayu, Aina Putri; Marpaung, Zaid Alfauza (LEGAL BRIEF, 2024)
This study aims to discuss the review of Islamic criminal law and national criminal law related to the combination of criminal acts in the case of prospective TNI AL NCO students in Padang, West Sumatra. This study applies the method of field legal research (legal research). The results of the study reveal that positive law adopts three theories that are combined in the concept of punishment, namely cumulative theory, absorption theory, and mixed theory. The three theories are listed in Articles 60 to 71 of the Criminal Code, regulating the combination of criminal acts of concursus idealis, concursus realis, and voortgezette handeling. The application of the combined theory of punishment in positive law is designed to comply with the principles of justice, benefit, and legal certainty. Conceptually, this idea has fundamental differences with Islamic criminal law. In positive law, various criminal acts carried out by one perpetrator are subject to one type of reward according to the provisions that the criminal acts are carried out in a close time or continuously, so that they are included in ongoing actions. This provision is looser than Islamic law, recognizing the imposition of one punishment for several acts if the acts have the same purpose. If they have different purposes, the perpetrator must be given the appropriate punishment with the type of criminal punishment that has been committed